Quantification of increased biologically active CXCL12α plasma concentrations after ACKR3 antagonist treatment in humans - Peter Blattmann; Hervé Farine; Brian Dan; Nicole Stiffler; Thomas Lefebvre; Christine Huynh; Patricia N. Sidharta; Jasper Dingemanse; Richard W. D. Welford; Marcel Keller; Daniel S. Strasser (Wiley, 2024)
Abstract CXCL12 acts as a chemoattractant by binding to the receptor CXCR4. The (atypical) chemokine receptor ACKR3 (CXCR7) scavenges CXCL12. Antagonism of ACKR3 thus leads to an increase in CXCL12 concentrations that has been used as a pharmacodynamic biomarker in healthy adults. Increased CXCL12 concentrations have also been linked to repair mechanisms in human diseases and mouse models. To date, CXCL12 concentrations have typically been quantified using antibody‐based assays with overlapping or unclear specificity for the various CXCL12 isoforms (α, β, and γ) and proteoforms. Only the N‐terminal full‐length CXCL12 proteoform is biologically active and can engage CXCR4 and ACKR3, but this proteoform could so far not be quantified in healthy adults. Here, we describe a new and fit‐for‐purpose validated immunoaffinity mass spectrometry (IA‐MS) assay for specific measurement of five CXCL12α proteoforms in human plasma, including the biologically active CXCL12α proteoform. This biomarker assay was used in a phase I clinical study with the ACKR3 antagonist ACT‐1004‐1239. In placebo‐treated healthy adults, 1.0 nM total CXCL12α and 0.1 nM biologically active CXCL12α was quantified. The concentrations of both proteoforms increased up to two‐fold in healthy adults compared to placebo following drug administration. At all dose levels, 10% of the CXCL12α was the biologically active proteoform and the simultaneous increase of all proteoforms suggests that a new steady state has been reached 24 h following dosing. Hence, this IA‐MS biomarker assay can be used to specifically measure active CXCL12 proteoform concentrations in clinical trials to demonstrate target engagement and correlate with clinical outcomes.